1992
DOI: 10.1002/ffj.2730070104
|View full text |Cite
|
Sign up to set email alerts
|

On the genuineness of citrus essential oils. Part XXXIV. Detection of added reconstituted bergamot oil in genuine bergamot essential oil by high resolution gas chromatography with chiral capillary columns

Abstract: A rapid method for the detection of the addition of reconstituted bergamot oils to natural bergamot essential oils is suggested. The method is based on the ratio of the two enantiomers of linalol determined by gas chromatography with chiral capillary columns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 6 publications
2
10
0
Order By: Relevance
“…Since it was clearly shown that natural bergamot fl avour contains only one pure enantiomer or very high enantiomeric purities of the (R)-(−)-linalool and (R)-(−)-linalyl acetate, [10][11][12][13][14][15][16] the racemates and the other enantiomeric mixtures of those compounds in the commercial fl avoured teas and concentrate imply adulteration of the products. [17][18][19] The enantiomeric distribution of linalyl acetate and linalool was not changed during offi cinal steam distillation.…”
Section: Table 4 Enantiomeric Ratio (%) Of γ-Lactones In Passion Frumentioning
confidence: 99%
“…Since it was clearly shown that natural bergamot fl avour contains only one pure enantiomer or very high enantiomeric purities of the (R)-(−)-linalool and (R)-(−)-linalyl acetate, [10][11][12][13][14][15][16] the racemates and the other enantiomeric mixtures of those compounds in the commercial fl avoured teas and concentrate imply adulteration of the products. [17][18][19] The enantiomeric distribution of linalyl acetate and linalool was not changed during offi cinal steam distillation.…”
Section: Table 4 Enantiomeric Ratio (%) Of γ-Lactones In Passion Frumentioning
confidence: 99%
“…Regarding the volatile compounds from food materials, this fragmentation analysis has been first done. These results suggest that in addition to enantiomeric analysis 14,15) and isotope ratio analysis of the molecular ion peaks on mass spectra, [10][11][12] this technique for MS fragment isotope ratio analysis can provide diverse information on the evaluation of natural essential oils. This technique is also applicable to the compounds of which peaks on gas chromatograms are very small or a molecular ion peak on a mass spectrum is not detectable.…”
Section: Multivariate Analysis Of Carbonyl Fractionsmentioning
confidence: 99%
“…In general, chiral terpenic compounds (the structure of which contains one or more asymmetric carbon atoms, and exhibits optical activity) of natural origin and in specific species have a characteristic distribution of enantiomers that is attributable to stereoselectively-controlled biogenetic formation mechanisms of the respective plant (Werkhoff et al, 1993). Consequently, the enantiomeric separation of chiral terpenes has been advocated for the identification of adulteration of different products as these compounds can be distinctive to the aroma or relevant to establishing the natural or synthetic origin of a specific sample (Ravid et al, 2010;Cotroneo et al, 1992).…”
Section: Introductionmentioning
confidence: 98%